Supporting student teachers through their first attempts at teaching: Possibilities and limitations afforded by school-based and campus based models of support. - Rusznyak, L.; Moosa, M. (My University, 2014)
Student teachers' first attempt at teaching a lesson is a crucial step in their professional development. This paper compares the potential pedagogical learning opportunities and limitations afforded by school-based and campus-based support programmes that are designed to support student teachers in their early attempts at teaching. We use a qualitative analysis of interviews with university lecturers and a quantitative analysis of written feedback provided to student teachers within each of these models. The analysis of our data shows that during the school-based model, students receive retrospective feedback on many diverse issues relating to their lesson, particularly their management of learners. In contrast, the campus-based model offers student teachers an explicit opportunity to work collaboratively on the management of the content knowledge for their first lesson. The campus-based model, despite its numerous limitations, offers possibilities for developing students' understanding of teaching as a complex cognitive practice from their early attempts at teaching.